Peripheral loss of CD8+CD161++TCRVα7·2+ mucosal-associated invariant T cells in chronic hepatitis C virus-infected patients - Barathan, M.; Mohamed, R.; Vadivelu, J.; Chang, L.Y.; Saeidi, A.; Yong, Y.K.; Ravishankar Ram, M.; Gopal, K.; Velu, V.; Larsson, M.; Shankar, E.M. (Blackwell Publishing, 2016)
Background: Mucosal-associated invariant T (MAIT) cells play an important role in innate host defence. MAIT cells appear to undergo exhaustion and are functionally weakened in chronic viral infections. However, their role in chronic hepatitis C virus (HCV) infection remains unclear. Materials and methods: We investigated the frequency of CD8+CD161++TCR Vα7.2+ MAIT cells in a cross-sectional cohort of chronic HCV-infected patients (n = 25) and healthy controls (n = 25). Peripheral blood mononuclear cells were investigated for circulating MAIT cell frequency, liver-homing (CCR5 and CD103), biomarkers of immune exhaustion (PD-1, TIM-3 and CTLA-4), chronic immune activation (CD38 and HLA-DR), and immunosenescence (CD57) by flow cytometry. Results: The frequency of MAIT cells was significantly decreased, and increased signs of immune exhaustion and chronic immune activation were clearly evident on MAIT cells of HCV-infected patients. Decrease of CCR5 on circulating MAIT cells is suggestive of their peripheral loss in chronic HCV-infected patients. MAIT cells also showed significantly increased levels of HLA-DR, CD38, PD-1, TIM-3 and CTLA-4, besides CD57 in chronic HCV disease. Conclusions: Immune exhaustion and senescence of CD8+CD161++TCR Vα7.2+ MAIT cells could contribute to diminished innate defence attributes likely facilitating viral persistence and HCV disease progression.